PERAN PASAR MODAL BAGI INVESTASI DI INDONESIA - Basyarudin, Basyarudin; Ramadhan, Gilang (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The role of the capital market as a source of corporate funding that has an impact on the country's economy and not as an option but is able to become the main source of funding. This research aims to find out about how the role of the capital market for increasing investment in Indonesia. This research uses data collection techniques with interview, observation and documentation methods. The results of this study can be seen that the capital market has an important role in a country, one of which is to provide investment options for investors in Indonesia. With the capital market, investors get the opportunity to benefit from the investments that have been made. In addition, the capital market also provides opportunities for the community to increase national economic activity. Almost every country in the world has a capital market, including Indonesia, this aims to provide facilities for the needs of all entities in fulfilling the capital needed or invested.